2021
DOI: 10.3390/medicina57060521
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of SARS-CoV-2 Virus Infection on the Course of Atopic Dermatitis in Patients

Abstract: Background and Objectives: Atopic dermatitis (AD) is a disease with a complex pathophysiology involving immune-mediated reactions that lead to skin lesions that are typically localized and recurrent. Following the outbreak of the COVID-19 (coronavirus disease 2019) pandemic, attempting to assess the impact of SARS-CoV-2 infection on diseases caused by complex immune mechanisms has become important. The aim of this study was to assess the impact of SARS-CoV-2 infection on the course of AD, including immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…The patients with severe atopic dermatitis who were receiving immunosuppressive therapy had milder exacerbations. 16 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients with severe atopic dermatitis who were receiving immunosuppressive therapy had milder exacerbations. 16 …”
Section: Resultsmentioning
confidence: 99%
“…Another study assessed 21 adults with atopic dermatitis who had also been infected with COVID‐19 and found out that 43% of these patients experienced disease exacerbation that did not require systemic intervention. The patients with severe atopic dermatitis who were receiving immunosuppressive therapy had milder exacerbations 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a significant limitation of this study. However, a similar observational study in patients with atopic dermatitis and immunosuppressive therapy also found no effect on the severity of COVID-19 [ 18 ]. The possible negative effects of this type of therapy should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic conditions may be accompanied by skin lesions in which the innate immune system is involved [34,35]. Associated immune-mediated skin diseases, such as psoriasis, atopic dermatitis, and suppurative hidradenitis, have been reported [36,37].…”
Section: Skin Involvementmentioning
confidence: 99%